Upaya Meningkatkan Keterampilan Menulis Naskah Drama Peserta Didik Pkbm An-Nahar dengan Metode Latihan Terbimbing - Muh Akbar Kurniawan; Muhammad Halim Yahman; Muhtar Asari; Ahmad Nur Samsi (Journal on Education, 2023)
The background of this research is the result of an interview with one of the teachers while doing Field Experience Practice at PKBM An-Nahar. The results of the interviews revealed that students were still lacking interest when given writing assignments. Learning is done by lecture method. Meanwhile, students do not hone material outside of learning. Material arrest and consequences of students are very limited. practicing in writing skills training from students is expected to have a solution. This solution must also be able to foster passion and interest in writing. Based on the above, researchers will conduct research on efforts to improve the drama writing skills of PKBM An-Nahar students using the Guided Exercise Method. This research is included in the class action research (CAR). The research subjects were An-Nahar PKBM students, Kuwarasan, Kebumen. The variable taken in PTK is the skill of writing drama scripts with guided practice techniques. The indicators taken are in the form of quantitative and qualitative data. Based on the results of the research, data were obtained on the process aspect of growing students' interest in writing as many as 22 students (88%). In the aspect of the process of finding ideas as many as 20 students (80%). In the aspect of the process of financing the elements in writing, there were 20 students (80%). In the aspect of the writing process, it can be seen from the rules of writing a script as many as 18 students (72%). And in the aspect of whether students are conducive to writing, there are also 22 students (88%). From these data, it means that students experience a significant increase after learning with the guided practice method. It can be concluded that efforts to improve writing skills using guided practice methods have been successful.